Multi-element analysis of Ghanaian crude oils by instrumental neutron activation analysis - Appenteng, M.K.; Adomako, D.; Saka, D.; Golow, A.A.; Hayford, M.S.; Sarfo, D.K.; Carboo, D.; Yamoah, A.K.K. (Journal of Radioanalytical and Nuclear Chemistry, 2012)
Instrumental neutron activation analysis based on thermal neutrons from the Ghana Research Reactor-1 facility was utilized to analyze 18 trace elements namely Al, As, Br, Ca, Cd, Cl, Co, Cu, Fe, K, Mg, Mn, Na, Ni, S, Si, V, and Zn in two different crude oil samples from the Saltpond and Jubilee field in the Saltpond, Central region and Cape Three Points, Western region of Ghana, respectively. The sulfur concentration for both samples were low and within globally accepted range of 0.1-0.5%wt for sweet crude oil. The results of the elemental analysis showed that the two samples are relatively low in trace element concentrations compared to crude oils of other countries. Higher Fe concentration in the Jubilee crude oil indicates younger oil. The V/Ni ratios obtained for crude oils from both locations imply a possible marine organic origin and also suggest the Saltpond crude oil is more matured than the Jubilee crude oil. © 2011 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Instrumental neutron activation analysis; Jubilee crude oil; Saltpond crude oil; Trace elements